Memahami Kedudukan Pengadilan Tata Usaha Negara di Indonesia: Sistem Unity of Jurisdiction atau Duality of Jurisdiction : Sebuah Studi Tentang Struktur dan Karakteristiknya - Detaris Gulo; Diki Zukriadi (Lembaga Pengembangan Kinerja Dosen, 2024)
The two main different principles in judicial system in the various legal states are namely(first): as the unity of jurisdiction system applied by rule of law which only consisted of Civil court and, (second): the duality of jurisdiction system which applied by rechtstaat Law states that is known consisted of civil court and administrative court. Civil courtCulminates in the Supreme Court while the Administrative Court culminates in the StateCouncil (Conseil d’Etat). These two systems are not just different in court organizational hierarchy, but also different ini the legal substance and the legal procedural. TheResearch reports show that the Judicial system in Indonesia is very unique , from the Judicial organization alhierarchy perspective is closer to the system of unity ofJurisdiction, whereas from the principles of the court and the procedure of dispute Settlement perspective is closer to the duality of system jurisdicton so the authors finally Conclude that the judicial system of Indonesia is a mixture system.